2013
DOI: 10.1177/1010539513506602
|View full text |Cite
|
Sign up to set email alerts
|

Does the Experience of Discrimination Affect Health? A Cross-Sectional Study of Korean Elders

Abstract: This study was conducted among 992 Koreans aged 60 to 89 to examine the effects of perceived discrimination on the health of an ethnically homogenous older population. Perceived discrimination was measured with a self-report instrument. Health outcomes included depressive symptoms, poor self-rated health, and chronic diseases. Of the elderly Koreans surveyed, 23.5% reported having experienced discrimination based on education, age, birthplace, birth order, or gender. Among women, 23.1% reported experiencing ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the other hand, the experience of discrimination played a negative role in achieving SA in Koreans. Indeed, Chun et al 19 described in their study that 23.5% of older Koreans reported the experience of discrimination based on education, age, birthplace, or gender, and these experiences highly predicted depressive symptoms and a poor self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the experience of discrimination played a negative role in achieving SA in Koreans. Indeed, Chun et al 19 described in their study that 23.5% of older Koreans reported the experience of discrimination based on education, age, birthplace, or gender, and these experiences highly predicted depressive symptoms and a poor self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of Korean elders, the health impacts of education discrimination were the most prominent; however, men reported education discrimination more frequently than women. 26 Given that actual levels of education are lower in disadvantaged populations, they may also perceive more education discrimination. This is an interesting line of research and suggests education discrimination should be investigated in addition to racial or gender discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…In the mental-illness domain (outside of work environments), 95.5% of the 44 studies and 93.2% of the 88 associations found evidence of ageism influencing psychiatric conditions. The most frequently examined condition, depressive symptoms, showed evidence that ageism was associated with onset and lifetime depression, as well as increases in depressive symptoms over time [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. Reflecting a hopeful finding in this area, researchers found that when older persons resisted negative age stereotypes, they were less likely to experience suicidal ideation, anxiety, and PTSD in a nationally representative sample of American veterans [84].…”
Section: Impact Of Ageism On Health Of Older Persons: Individual Levelmentioning
confidence: 99%